Tuning the nitrogen-doping configuration in carbon materials via sulfur doping for ultrastable potassium ion storage. Issue 29 (16th July 2021) - Xu, Yang; Wang, Changlai; Niu, Ping; Li, Zhiqiang; Wei, Lingzhi; Yao, Ge; Zheng, Fangcai; Chen, Qianwang
Abstract : We successfully achieve high-level pyridinic-N and pyrrolic-N in nitrogen-doped carbon materials, which exhibits a high reversible capacity (441.5 mA h g −1 over 100 cycles at 0.1 A g −1 ) and long-term cycling stability (283.3 mA h g −1 after 1000 cycles at 2 A g −1 ). Abstract : Nitrogen doping is a promising strategy to improve the potassium-storage performances of carbon materials. It is found that graphitic-N, pyridinic-N and pyrrolic-N always coexist in nitrogen-doped carbon materials prepared by typical synthesis techniques. However, graphitic-N is demonstrated to be unfavorable for the adsorption of potassium ions (K + ). Therefore, achieving high-level nitrogen species of pyridinic-N and pyrrolic-N is still a big challenge. Herein, we successfully tune the nitrogen configuration and achieve high-level (85.0%) pyridinic-N and pyrrolic-N in nitrogen-doped carbon materials via sulfur doping. The resulting sulfur-doped nitrogen rich carbon materials (S/N-CMs) exhibit a high reversible capacity of 441.5 mA h g −1 over 100 cycles at 0.1 A g −1, superior rate capability (160.4 mA h g −1 at 5 A g −1 ), and long-term cycling stability (283.3 mA h g −1 after 1000 cycles at 2 A g −1 ). The potassium-storage performances are superior to those of most of the carbon materials for potassium ion batteries (KIBs). Density Functional Theory (DFT) calculations confirm that pyridinic-N and pyrrolic-N improve the adsorption ability of K + in carbon materials, and sulfur doping can further improve the potassium-storage performances of nitrogen-doped carbon materials, synergistically ensuring high potassium-storage capacity and cycling stability for S/N-CMs.